–ED ALLOMORPHS AND LINGUISTIC KNOWLEDGE OF MALAY SPEAKERS OF ENGLISH: A DESCRIPTIVE AND CORRELATIONAL STUDY - Lotfie, Maskanah Mohammad; Kadir, Maimunah Abdul; Pilus, Zahariah (Universitas Pendidikan Indonesia, 2017)
Malay is a language from the Austronesian family and unlike the Indo-European-originated English, it does not generally have inflectional temporal markers. Investigating this from a cross-linguistics - influence perspective, differences between the languages could mean difficulties for Malay speakers to acquire features of English. The objectives of this study are to investigate Malay speakers’ pronunciation of the English language –ed allomorphs – [d], [t] and [ɪd]/[əd] – and the relationship between the morphophonological forms and two types of linguistic knowledge, one of which is implicit while the other is explicit. Data were collated from fifty participants who are social science undergraduates and English majors who speak English as a second language. Four instruments were used to gauge the respondents’ verbal use of –ed allomorphs as well as their implicit and explicit knowledge of the allomorphs. Results indicate that the students’ verbal usage of the target items either lacks approximation to Standard English pronunciation or is largely dropped altogether. Results also suggest a moderate relationship between implicit and explicit knowledge of the allomorphs and their verbal production by Malay speakers of English. The finding illuminates acquisition problem of English language speakers whose mother tongue does not share similar inflectional markers. Pedagogical solutions can help learners of the English language to approximate Standard English and in the long run, enhance effective communication and increase chances of employability.